Smart Mines and Intelligent Mining - Li, Hang (International Journal of Natural Resources and Environmental Studies, 2026)
As a crucial energy resource, coal plays a pivotal role in the global energy mix. This is particularly evident in China. Endowed with abundant reserves, the country relies on coal as its primary energy source. However, traditional extraction methods are fraught with challenges, including resource depletion, environmental degradation, and significant safety hazards. Consequently, the advancement of intelligent mining technologies is of paramount importance. These innovations enhance resource utilization efficiency, mitigate environmental impacts, and safeguard the well-being of miners. Intelligent coal mining leverages modern information systems, automation, and artificial intelligence to achieve a fully automated, informatized, and smart extraction process. In this context, "intelligence" denotes a comprehensive system capability. It encompasses the real-time, precise perception of data objects, alongside rapid and accurate decision-making support. Furthermore, it involves efficient execution coordination and the autonomous ability to analyze, judge, and act upon external stimuli, coupled with the capacity for independent learning and process optimization. Recent years have witnessed remarkable technological breakthroughs in this domain. These advancements are primarily driven by the integration of big data, artificial intelligence, the Internet of Things (IoT), advanced sensor technologies, and 5G+ networks. By systematically aggregating mine production data, big data and AI have substantially elevated the sophistication of production management. Concurrently, IoT and sensor technologies facilitate the real-time monitoring of mine environments and equipment operational status, thereby ensuring absolute data accuracy and immediacy.